Annual Plan Proposals 1966-67 Dadra and Nagar Haveli - Planning Commission (Planning Commission, 1964)
The report presents a comprehensive overview of various agricultural schemes and initiatives aimed at improving dairy farming and agricultural productivity. It discusses the development of supply chains for implements, seeds, and manures, as well as the establishment of dairy farms to provide pure milk to local inhabitants. The financial aspects, including expenditures and budget allocations for different schemes over the years, are detailed, highlighting the importance of structured planning and resource management in agricultural development.
Dadra and Nagar Haveli
Keywords: Dairy Farming; Agricultural Schemes; Supply Chains; Financial Expenditures; Resource Management; Pure Milk Provision; Development Initiatives; Budget Allocations; Training Staff; Agricultural Productivity